ANALISIS PENERAPAN PEMBELAJARAN PBL PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV UNTUK MEMBENTUK PROFIL PELAJAR PANCASILA ELEMEN BERPIKIR KRITIS - Kartika Ayu Hapsari; Suyoto; Nur Ngazizah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The lack of understanding on how to Problem-Based Learning (PBL) and the suboptimal critical thinking skills of students due to curriculum transition are the background of this research. This research aims to analyze the implementation of PBL in shaping the profile of Pancasila students with critical thinking elements. The research method used is descriptive qualitative with a sample of 15 fourth-grade students and 1 class teacher selected through purposive sampling technique. The results show that the implementation of PBL is in accordance with the PBL syntax and can improve students' critical thinking skills, with good mastery in expressing opinions (73.33%), but 66.7% of students still require guidance in identifying assumptions and biases. The main conclusion of this research is that the implementation of PBL is effective in shaping the profile of Pancasila students with critical thinking elements. The implications of this research include theoretical and practical aspects, as well as opening up opportunities for further studies on the effectiveness of PBL.